High spin states of Ar 37 - Das A.; Bisoi A.; Sarkar M.S.; Sarkar S.; Ray S.; Pramanik D.; Kshetri R.; Nag S.; Singh P.; Selvakumar K.; Goswami A.; Saha S.; Sethi J.; Trivedi T.; Naidu B.S.; Donthi R.; Nanal V.; Palit R. (My University, 2025)
High spin states of Ar37, populated through the Al27(C12,np)Ar37 reaction with a 40 MeV C12 beam, were studied using the Indian National Gamma Array (INGA) facility. The existing level scheme has been extended up to 10.5 MeV by adding some new levels and transitions. The spins and parities of the new levels were assigned from RDCO, RADO, and linear polarization measurements. The spins and parities of the existing levels also were modified or confirmed in the present experiment. The multipole mixing ratios (δ) for most of the transitions were measured and compared with the earlier measurements wherever available. Large basis shell model calculations with different particle restrictions in sd and pf orbitals were performed to understand the microscopic origin of these levels. A simple two-level mixing calculation was also performed to extract the amount of multiparticle multihole configuration mixing for a few levels. © 2020 American Physical Society.